Does Mandatory Saving Crowd Out Voluntary Saving? Evidence from a Pension Reform - Svend E. Hougaard Jensen; Sigurdur P. Olafsson; Arnaldur Stefansson; Thorsteinn Sigurdur Sveinsson; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2022)
Recently, mandatory pension contributions in the private sector in Iceland were increased substantially while remaining unchanged in the public sector. This constituted a large natural experiment. We study the effects of this experiment on households' voluntary saving using administrative micro data with comprehensive third-party reported information on taxpayers' income, assets and debt for all taxpayers in the country. Using difference-in-differences, we find that households do not reduce voluntary saving when faced with a rise in mandatory saving. Our results are confirmed by the finding that workers who move between the public and the private sector, which have different mandatory saving rates, do not change their voluntary saving behavior. Our survey evidence suggests that these findings may be explained by widespread ignorance about the pension system.
Keywords: E21; E24; 330; pension reform; occupational pensions; saving; retirement